Electronic Medical Records Implementation at Soeradji Tirtonegoro Hospital, Klaten, Indonesia - atma deharja; Dito Yogo Waskito; Ervina Rachmawati; Veronika Vestine (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Soeradji Tirtonegoro Hospital uses Electonic Medical Records (EMRs) to transform health technology. EMR filling completeness in the outpatient clinic was only 74.3% in June 2022, below the 100% service standard. This study aimed to analyze the factors causing the implementation problem of EMR in Soeradji Tirtonegoro Hospital—a quantitative analysis with a cross-sectional study was conducted, adapted from Mandatory Use of Software Technologies (MMUST) Model. The respondents totaled 108 people, including doctors, nurses, midwives, and medical recorders. Data analysis was performed using SmartPLS 3.2.9 with the SEM-PLS technique. This study showed a significant relationship between the variable's information quality and information satisfaction with a T-statistic value of 10.377. Furthermore, information satisfaction towards performance expectations (5,711) and performance expectations towards attitude (6,063). Social influence also affects performance expectations (2.660). Facility conditions affect attitude (2.145), attitudes towards overall satisfaction (26,209), and overall satisfaction with net benefits (10,876). However, there are two insignificant variable relationships: attitude towards use (0,367) and use towards net benefits (1.393). Based on the study, it is concluded that all exogenous variables influence the endogenous variable. However, there are two insignificant variable relationships. Hopefulness, future research can modify the model by adding control variables using the effect of confounding factors such as officer work schedules.